“I thought I was going to pass”: Learners’ experiences of grade retention - Maureen Hadebe; Moeniera Moosa (South African Journal of Education)
Grade retention is the practice of holding back learners who have failed to meet specific promotional requirements as stipulated by policy, in the same grade. The main objective of the research reported on here was to determine Foundation Phase (Grades 1–3) learners’ experiences and perceptions of grade retention. The theoretical framework used was Messiou’s (2006) conceptualisation of marginalisation. In this study we employed a phenomenographic, qualitative research approach. Twelve participants who had repeated grades in the Foundation Phase at a school in Johannesburg, South Africa, were purposively selected. Data were collected by means of one-on-one interviews, “blob trees”, drawings, and collages from participants about their views and experiences of retention. The findings of this study reveal that learners were not psychologically prepared to be retained. Most learners experienced being bullied by their peers and teachers due to being retained, which led to them feeling excluded and marginalised. A correlation was found between parents’ and teachers’ views of retention and learners’ experiences. Future research should focus on learners’ experiences of retention at different schools and in different school phases in South Africa.